Codification, confusion and crisis: police-government relations when responding to February 2022 protests in Ottawa and Wellington - Roach, Kent (Policing and society, 2025)
This article examines whether the codification of police government relations makes a difference in a crisis. Drawing on detailed official reports about similar protests and occupations of capitals in Ottawa, Canada and Wellington, New Zealand in February 2022, it concludes that codification did not make an appreciable difference to either governmental or police conduct. Governing bodies were reluctant to take responsibility for policing decisions even when they had unfettered statutory powers to do so. At the same time, New Zealand politicians may have pressured the New Zealand Police to engage in an early and unsuccessful attempt to clear the occupation despite broad statutory guarantees of police operational independence, even though the politicians, the police and the inquiry all denied that there was political interference. The article clarifies thinking about police independence by problematising the idea of police operational independence by focusing on policy of operations decisions, specifically whether the police should wear riot gear when policing protests. It also examines the under-studied issue of the relevance of the police chain of command under different conceptions of police independence. It concludes that codification alone will not make police-government relations more transparent or democratic.